Hypoxia during resistance exercise does not affect physical performance, perceptual responses, or neuromuscular recovery - Scott, B. R.; Slattery, K. M.; Sculley, D. V.; Dascombe, B. J. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to determine whether performing resistance exercise in hypoxia affects markers of physical performance, perceptual responses, and neuromuscular function. Fourteen male subjects (age: 24.6 ± 2.7 years; height: 179.7 ± 5.9 cm; body mass: 84.6 ± 11.6 kg) with >2 years resistance training experience performed moderate-load resistance exercise in 2 conditions: normoxia (FIO2 = 0.21) and hypoxia (FIO2 = 0.16). Resistance exercise comprised 3 sets of 10 repetitions of back squats and deadlifts at 60% of 1 repetition maximum (1RM), with 60 seconds inter-set rest. Physical performance was assessed by quantifying velocity and power variables during all repetitions. Perceptual ratings of perceived exertion, physical fatigue, muscle soreness, and overall well-being were obtained during and after exercise. Neuromuscular performance was assessed by vertical jump and isometric mid-thigh pull (IMTP) tasks for up to 48 hours after exercise. Although physical performance declined across sets, there were no differences between conditions. Similarly, perceived exertion and fatigue scores were not different between conditions. Muscle soreness increased from baseline at 24 and 48 hours after exercise in both conditions (p = 0.001). Jump height and IMTP peak force were decreased from baseline immediately after exercise (p = 0.026), but returned to preexercise values after 24 hours. These findings suggest that hypoxic resistance exercise does not affect exercise performance or perceived exercise intensity. In addition, neuromuscular recovery and perceptual markers of training stress were not affected by hypoxia, suggesting that hypoxic resistance training may not add substantially to the training dose experienced.